Capital and finance in agriculture; report. - Organisation for Economic Co-operation and Development ([Paris] Organisation for Economic Co-operation and Development, 1970)
The first part of the study deals with the tendencies in the use of capital, analyzing the trend in various types of capital, differences between countries, regions, types of farm, etc. The second part aims to show how agriculture has financed its investments and in particular to what extent it has been necessary to resort to credit
Includes bibliographical references.
osc 31/01/2019
Loans
Keywords: Capital; Agriculture; Agricultural finance